Prescription practices in acute pediatric infections - Shiva, Farideh; Eidikhani, Abdul-Latif; Padyab, Mojgan (Journal of Pediatric Infectious Diseases, 2006)
Optimal medical care requires that patients receive medications appropriate to their clinical needs. To achieve this objective it is essential that irrational patient management practices are identified, and attempts made towards their correction. A study was done in Tehran to identify prescribing practices in common acute infections in children. Data collected from reviewing the prescriptions given to children in three different settings of ambulatory care, and from interviewing their parents, was documented on a structured questionnaire. Five hundred prescriptions were reviewed. Three hundred and eight were for acute gastroenteritis and 192 for acute respiratory tract infection. The average number of drugs/prescription was 3.33 ± 1.2; general practitioners prescribed 3.47 ± 1.2 and pediatricians 3.2 ± 1.1 drugs, (P = 0.032). Antibiotics were written in 79.4%, and 42.8% included injections. In respiratory infections, antihistamines were prescribed in 73.4%. In gastroenteritis anti-emetics were written for 62% and 61.4% were not given oral rehydration solution (ORS). General practitioners prescribed more medications and less ORS than pediatricians. The difference was statistically significant for injections, ORS and anti-emetic medications (P < 0.05). More drugs/prescription and more antibiotics were given in private clinics as compared to public hospitals (P < 0.05). We identified inappropriate drug use in acute respiratory and gastrointestinal infections in children receiving outpatient care in Tehran. Before planning successful intervention strategies, it is crucial to develop insight in the socio-cultural incentives that result in irrational prescriptions.
Keywords: Prescriptions; acute respiratory infection; gastroenteritis